W.D. Cole correspondence - Cole, W. D. (William Duncan)
ALS (1862 June 9; Camp Holt, Mobile, Alabama) from Cole of the 38th Alabama Infantry Regiment to his wife, Cornelia A. Cole, describing camp life and Confederate fortifications in the Mobile area. Includes cover.
Confederate soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Cole, Cornelia A. -- Correspondence; Confederate States of America. -- Army -- Military life; Confederate States of America. -- Army. -- Alabama Infantry Regiment, 38th.; Fortification -- Alabama -- Mobile; Alabama -- History -- Civil War, 1861-1865.; Confederate States of America -- History; Mobile (Ala.) -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Soldiers